HUBUNGAN BILATERAL PEMERINTAH REPUBLIK INDONESIA DAN PEMERINTAH AUSTRALIA DALAM BIDANG EKONOMI KREATIF - Adi Joko Purwanto; Isma Wati (LP2M, 2019)
Abstract The process of globalization of a country with other countries aimed at meeting the needs of the people and for the interests of countries in the world. Cooperation relations between countries are needed for the necessities of life and the existence of a state in international social relations, in addition to the creation of peace and prosperity which is the dream of every human being and the country in the world. Each country has different advantages, disadvantages and interests. These are the things that encourage international relations and cooperation. The author uses constructivism theory that goes into the study of international relations which emphasizes the importance of ideas, identity, in determining interests. Then the world order will understand the constructivist view of the bilateral relations between Indonesia and Australia in the creative economy. Keywords: bilateral, Indonesia, Australia, creative economy.